A meta-analysis of the effect of physical activity programs on fundamental movement skills in 3–7-year-old children - Yang, Yunjiao; Mao, Xiaojin; Li, Wenhao; Wang, Botian; Fan, Lixia (Frontiers in Public Health, 2025)
IntroductionThis study aimed to systematically review the effects of different physical activity programs on the fundamental movement skills of 3 - 7-year-old children.MethodsFor this review, the databases of CNKI, Web of Science, and PubMed were searched to collect relevant literature on the effects of different physical activity program interventions on fundamental movement skills, and a total of 10 articles with 1,121 subjects were included. The Cochrane Risk of Bias Assessment Tool was used to assess the quality of the literature, and meta-analysis was performed using Review Manager 5.4 software.ResultsPhysical activity significantly influenced children’s running ability, horizontal jump, dribbling the ball, kicking ability, catching ability, overhand throwing, striking a stationary ball, and dynamic balance. However, the intervention effect was insignificant for the hop and underhand throwing abilities. The intervention effects for running ability, horizontal jump, kicking ability, and catching ability were better at less than 12 weeks than at 12 weeks and above. In addition, an intervention duration of 90 min or more was better than less than 90 min for running ability and horizontal jump.ConclusionFuture research is recommended to focus on the common factors of the intervention effects of physical activity programs to develop more precise and effective intervention practices to further improve children’s fundamental movement skill levels.